Mechanisms of CNS Viral Seeding by HIV+ CD14+ CD16+ Monocytes: Establishment and Reseeding of Viral Reservoirs Contributing to HIV-Associated Neurocognitive Disorders - Mike Veenstra (American Society for Microbiology, 2017)
ABSTRACT HIV reservoirs persist despite antiretroviral therapy (ART) and are established within a few days after infection. Infected myeloid cells in the central nervous system (CNS) may contribute to the establishment of a CNS viral reservoir. The mature CD14+ CD16+ monocyte subset enters the CNS in response to chemokines, including CCL2. Entry of infected CD14+ CD16+ monocytes may lead to infection of other CNS cells, including macrophages or microglia and astrocytes, and to release of neurotoxic early viral proteins and additional cytokines. This contributes to neuroinflammation and neuronal damage leading to HIV-associated neurocognitive disorders (HAND) in ~50% of HIV-infected individuals despite ART. We examined the mechanisms of monocyte entry in the context of HIV infection and report for the first time that HIV+ CD14+ CD16+ monocytes preferentially transmigrate across the blood-brain barrier (BBB). The junctional proteins JAM-A and ALCAM and the chemokine receptor CCR2 are essential to their preferential transmigration across the BBB to CCL2. We show here that JAM-A and ALCAM are increased on HIV+ CD14+ CD16+ monocytes compared to their expression on HIVexp CD14+ CD16+ monocytes—cells that are uninfected but exposed to HIV, viral proteins, and inflammatory mediators. Antibodies against JAM-A and ALCAM and the novel CCR2/CCR5 dual inhibitor cenicriviroc prevented or significantly reduced preferential transmigration of HIV+ CD14+ CD16+ monocytes. This indicates that JAM-A, ALCAM, and CCR2 may be potential therapeutic targets to block entry of these infected cells into the brain and prevent or reduce the establishment and replenishment of viral reservoirs within the CNS. IMPORTANCE HIV infects different tissue compartments of the body, including the central nervous system (CNS). This leads to establishment of viral reservoirs within the CNS that mediate neuroinflammation and neuronal damage, contributing to cognitive impairment. Our goal was to examine the mechanisms of transmigration of cells that contribute to HIV infection of the CNS and to continued replenishment of CNS viral reservoirs, to establish potential therapeutic targets. We found that an HIV-infected subset of monocytes, mature HIV+ CD14+ CD16+ monocytes, preferentially transmigrates across the blood-brain barrier. This was mediated, in part, by increased junctional proteins JAM-A and ALCAM and chemokine receptor CCR2. We show that the CCR2/CCR5 dual inhibitor cenicriviroc and blocking antibodies against the junctional proteins significantly reduce, and often completely block, the transmigration of HIV+ CD14+ CD16+ monocytes. This suggests new opportunities to eliminate infection and seeding or reseeding of viral reservoirs within the CNS, thus reducing neuroinflammation, neuronal damage, and cognitive impairment.